Protective effect of Glycyrrhizic Acid against diclofenac-induced renal damage in male albino rats - Ayat Abdaljabar Al-kubaise; Ayyad W. Al-Shahwany (Iraqi Journal of Science, 2024)
Acute renal injury is a serious condition of severe damage to the kidney tissue resulting from various causes. Some medicinal plants have been used to treat certain renal injury. The purpose of the current investigation was to determine the protective effect of Glycyrrhizic acid (GA) on kidney function in rat models with induced kidney damage by Diclofenac sodium (Voltarene®, 50 mg coated tablets). Glycyrrhizic acid was given at doses of 200 and 400 mg/kg/day orally for 30 days. Its protective effect was evaluated by renal function tests . The result showed significant decreased the elevation of urea , serum creatinine and uric acid. Also, The result show significant decrease in total cholesterol, triglyceride concentration and low-density lipoprotein, and a significant increase in high-density lipoprotein concentration. Therefore, GA can be used for the prevention and treatment of renal damage and some kidney and liver disorders.